KETERAMPILAN HUBUNGAN SOSIAL SANTRI DI PESANTREN - Istihana, Istihana (Universitas Islam Negeri Raden Intan Lampung, 2015)
Islamic Boarding school is one of the non-formal education, to provide space for young muslims. Along with the demands higher especially in terms of social skill to walk life in world modern. Seems to have gained recognition as boarding powerful of citizens as the Islamic education institution that it is not only students to equip the religious side, but also, no less important is the legitimate skill for social life. This is what makes boarding there is now no longer seen as education deficit, which is identical to an educational institution and considered a second-class.It was indicated with the Islamic Boarding school to the peculiarities of each, and excellence so the public school education of one who mimics the boarding or boarding which recognized by there is Islamic boarding school.